STRATEGY FOR DISCREDITING SPEECH IN A VIRTUAL COMMUNICATION ENVIRONMENT (TAMADDUN NURI JURNALI, 2025)
Today, information communication technology covers all areas. In particular, the process of virtual communication through social networks is even more advanced. This article highlights strategies for virtual communication and discrediting speech on social media.